Business Modelling: A Case Study of a SME Grocery Business in Mantin, Malaysia - Yap, Olivia Walter (2016)
The objective of this research is to identify and explain real world SME grocery business in Malaysia, followed by the development of a suitable model based on the identified business model canvas (BMC) integrated into the balanced scorecard (BSC) to measure the level of performance in the organization and for transforming the business to improve business outcome (profit and sustainability). Literature reviewed has shown the need to identify and explain BMC for SME grocery business despite the various methods evolved over the years to remain competitive in the business environment; there are no effective performance measures to maintain the sustainability of SME grocery businesses. Measurement tools are only effective when the size of grocery business is greater than SME model identified as these provide practical information for grocery business to improve as a whole and remain sustainable in the competitive environment. This research applies change management theory as the theoretical foundation and reviews relevant literature to achieve research objective. It will adopt a qualitative case study approach with a single case design and collect data using face-to-face interviews. Subjects for this research are the owner and employee of selected grocery business which is Yap’s Market situated in Mantin, Malaysia.